PENGARUH INFLASI, NILAI TUKAR DAN SUKU BUNGA TERHADAP RETURN SAHAM SEKTOR TRANSPORTASI DAN LOGISTIK - Adeliya, Dita; Kencana, Dwi Tirta; Rosmala Sari, Tri Darma (AKUNTANSI DEWANTARA, 2024)
This study plans to decide the impact of inflation, exchange rate and interest rate on stock returns in the transportation and logistik area. The strategy utilized in this study is panel regression analysis, to determine the effect of each independent variable on the dependent variable. With the aim of knowing a comprehensive picture of the effect of inflation, interest rates and exchange rates on stock returns. The population of this study is the transportation and logistics sector listed on the Indonesia Stock Exchange for the 2019-2022 period. Samples were taken using purposive sampling technique and Data collection of stock prices, exchange rates, inflation, interest rates based on the official website.